(untitled) (Journal of Medicine, 2022)
Background: Vitamin D level has profound clinical implications but there is dilemma of optimal vitamin D cut-off level among Bangladeshi population as well in many parts of the world. This study aimed to determine the sufficient level of vitamin D [25 hydroxyvitamin D, 25(OH)D] in relation to intact parathormone (iPTH) in apparently healthy adult volunteers. Materials and Methods: This cross-sectional study was carried out among 130 apparently healthy adult participants [age (years): 37.57±12.23, mean±SD; m/f: 67/63] in Bangabandhu Sheikh Mujib Medical University, Dhaka. Demographic profile, sunlight exposure and dietary history were taken, physical examinations were done and fasting blood was taken to measure 25(OH)D, iPTH, calcium, albumin and phosphate. Serum 25(OH)D was measured by high performance liquid chromatography whereas iPTH, serum calcium, albumin and phosphate were measured by chemiluminescent Method. Results: The mean serum 25(OH)D of apparently healthy Bangladeshi adults was 15.44 – 18.44 ng/ml. Vitamin D level was significantly affected by age group [p=0.002], sunlight exposure time [p=0.013] and body surface area [p=0.023] along with sunscreen use [p=0.026]. Serum 25(OH)D had negative predictive association with iPTH [β=-0.220, p=0.012] and positive predictive association with daily sunlight exposure time [β=0.235, p=0.007]. Serum 25(OH)D level above 30 ng/ml was sufficient to keep maximum suppression of iPTH at 54.56 pg/ml by using the quadratic model. Conclusion: The optimal level of 25(OH)D for apparently healthy adults in Bangladesh is above 30.0 ng/ml. J MEDICINE 2022; 23: 139-145